2017
DOI: 10.1158/2326-6066.cir-16-0380
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Balance of Activating and Inhibitory Natural Killer Receptor Ligands on BRAFV600E Melanoma Lines with Vemurafenib

Abstract: Over 60% of human melanoma tumors bear a mutation in the gene. The most frequent mutation is a substitution at codon 600 (V600E), leading to a constitutively active BRAF and overactivation of the MAPK pathway. Patients harboring mutated BRAF respond to kinase inhibitors such as vemurafenib. However, these responses are transient, and relapses are frequent. Melanoma cells are efficiently lysed by activated natural killer (NK) cells. Melanoma cells express several stress-induced ligands that are recognized by ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Indeed, even though no evidence is reported so far in cancer cells, CO plays a pivotal role in reducing immune cell functions. 21 It is important to note that B7H6 and ULBP3 are expressed on MeOV-1 cells (up to 30 and 80% of positive cells, respectively), while ULBP1 and ULBP2 are not detectable. 20 They also showed that melanoma cell exposure to histone deacetylase inhibitors, known for their ability to increase the expression of ligands for NK activator receptors, 40 restored NK-mediated killing.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Indeed, even though no evidence is reported so far in cancer cells, CO plays a pivotal role in reducing immune cell functions. 21 It is important to note that B7H6 and ULBP3 are expressed on MeOV-1 cells (up to 30 and 80% of positive cells, respectively), while ULBP1 and ULBP2 are not detectable. 20 They also showed that melanoma cell exposure to histone deacetylase inhibitors, known for their ability to increase the expression of ligands for NK activator receptors, 40 restored NK-mediated killing.…”
Section: Discussionmentioning
confidence: 95%
“…Both IL-15-activated NK cells (Figs. 21 However, the NK-mediated lysis of PLX4032-treated MeOV-1 cells did not increase upon mAb-mediated masking of HLA class I molecules with a specific mAb of IgM isotype (data not shown), thus suggesting that the reduction in NK cell lysis of BRAFi-treated MeOV-1 cells could rather reflect a decreased expression of ligands of activating NK receptors. 5c and 5d) were used as effectors.…”
Section: Ho-1 Silencing Restores the Ability Of Nk Cells To Degranulamentioning
confidence: 86%
See 3 more Smart Citations